Evaluation of some mechanical properties of dental alginate impression materials after fluoride addition - Hummud, israa (Iraqi National Journal of Nursing Specialties, 2012)
Objective:Fluorid-containing dental alginate impression materials can exert a considerable reduction in enamel solubility. The objective was to evaluate the effect of fluoride addition on the setting time and compressive strength of alginate impression materials. Methodology: 60 samples were constructed from alginate impression material (30 samples for setting time test and 30 samples for compressive strength test).Specimens of each test divided into three subgroup. Group A: 10 specimens of alginate were mixed with distilled water [control], Group B: 10 specimens of alginate were mixed with100-ppm fluoride and Group C:10 specimens of alginate were mixed with 2%Naf. Results: the result of setting time test showed that addition of 2% Naf to alginate impression materials were delayed the setting reaction while the results of compressive strength test showed that high mean values were obtained from control group while group mixed with 2%Naf had lower compressive strength. Recommendation: it can be concluded that addition of 100-ppm fluoride were affect on the properties of alginate impression materials while addition of 2% Naf was deteriorated the properties of alginate impression materials. So recommends the effect of fluoride addition in other concentration